Thickened oil modification catalyst as well as preparation method and application thereof

By preparing and modifying magnetic iron tetraoxide nanocrystalline catalyst, the existing heavy oil modified catalyst has solved the problems of long reaction time, high pressure and large energy consumption, and the effective viscosity reduction and fluidity improvement of heavy oil have been achieved.

CN119456037AInactive Publication Date: 2025-02-18SHENGLI XINGKE PETROLEUM TECH DEV (SHANDONG) CO LTD +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202510048361.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing heavy oil modification catalysts have problems such as long reaction time, high reaction pressure and large energy consumption in reducing the viscosity of heavy oil. At the same time, hydrogen supply agents such as hydrogen gas are required, which is difficult to implement and high cost.

Method used

By preparing magnetic iron tetraoxide nanocrystals and modifying the epoxy silane coupling agent on its surface to couple with bisalicylic aldehyde-triethylamine Schiff base, then complexing nickel and iron ions and oleic acid Coated to produce a heavy oil modification catalyst.

Benefits of technology

This catalyst has good hydrothermal decomposition and cycle durability, which can effectively reduce the viscosity of heavy oil, promote the depolymerization of asphaltene aggregates, reduce the content of gum and asphaltene, thereby improving the fluidity of heavy oil.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a heavy oil modification catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalysts. The preparation method comprises the following steps: preparing magnetic ferroferric oxide nanocrystals, modifying the surfaces of the magnetic ferroferric oxide nanocrystals by using an epoxy silane coupling agent, coupling the modified magnetic ferroferric oxide nanocrystals with bis-salicylaldehyde-triethylamine Schiff base, complexing nickel and iron ions, and coating oleic acid on the surfaces of the modified magnetic ferroferric oxide nanocrystals to prepare the heavy oil modification catalyst. The heavy oil modification catalyst prepared by the invention has better hydrothermal decomposition performance and cycle durability, promotes degradation of heavy oil, promotes depolymerization of asphaltene aggregate, and finally reduces the content of colloid and asphaltene, so that the viscosity of the heavy oil is well reduced, and the heavy oil modification catalyst has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a heavy oil reforming catalyst and a preparation method and application thereof. Background Art

[0002] Due to the high viscosity of heavy oil, the fluidity of heavy oil deteriorates during the production and gathering process, the flow resistance increases, and the lifting of the wellbore and the long-distance transportation of the oil pipeline become very difficult. The high content of heavy components such as colloid, asphaltene, wax, etc. in heavy oil makes it have high viscosity characteristics; the high content of heavy metals, sulfides and mechanical mixtures makes it have high density characteristics. Compared with light crude oil, the content of saturated and aromatic components in the four components of heavy oil is lower, and the content of colloid and asphaltene is higher. Therefore, the catalytic modification and viscosity reduction technology of heavy oil is to improve its fluidity, and improving the quality of heavy oil is the key to solving the problems of heavy oil production, gathering and refining.

[0003] Existing disclosed heavy oil reforming catalyst technologies include: ① A catalytic modifier for hydrothermal cracking of downhole heavy oil made of molybdenum salt, distilled water and alkaline solution, with a reaction temperature of 180-280°C, a reaction time of 24-48h, and a viscosity reduction rate of about 90% for general heavy oil and super heavy oil under high pressure conditions of more than 6MPa. This technology has the disadvantages of long reaction time (>24h) and high reaction pressure (>6MPa). The viscosity reduction method disclosed in invention patent CA1195639 and invention patent application CN101649734A has the disadvantages of high reaction temperature (>370°C) and high energy consumption.

[0004] ② A method using ferrous or ferric oxides, sulfides and sulfates as catalysts to hydrothermally crack heavy oil into light hydrocarbons under the action of external hydrogen.

[0005] ③ A process using alumina loaded nickel and molybdenum as catalysts to hydrothermally catalytically crack heavy oil in an atmosphere of methane and hydrogen.

[0006] The above-mentioned heavy oil reforming catalysts need to add hydrogen, methane, etc. when catalyzing the viscosity reduction of heavy oil, which is difficult to implement and has high costs. Summary of the invention

[0007] The purpose of the present invention is to provide a heavy oil reforming catalyst and its preparation method and application, which has good hydrothermal decomposition performance and cycle durability, promotes the degradation of heavy oil, promotes the depolymerization of asphaltene aggregates, and ultimately reduces the content of colloid and asphaltene, thereby greatly reducing the viscosity of heavy oil, and has broad application prospects.

[0008] The technical solution of the present invention is achieved in this way: The invention provides a method for preparing a heavy oil reforming catalyst. After preparing magnetic ferrosoferric oxide nanocrystals, the surface is modified by an epoxy silane coupling agent, coupled with a disalicylicaldehyde-triethylamine Schiff base, and then nickel and iron ions are complexed. The surface is coated with oleic acid to prepare the heavy oil reforming catalyst.

[0009] As a further improvement of the present invention, the following steps are included: S1. Preparation of magnetic ferroferric oxide nanocrystals: dissolving iron salt and sodium oleate in a mixed solvent, heating and stirring the reaction, standing to separate the liquids, washing the upper reddish brown liquid with water, removing the solvent under reduced pressure to obtain ferrooleate, dissolving ferrooleate in petroleum ether to obtain a petroleum ether solution of ferrooleate, heating paraffin, dropping the petroleum ether solution of ferrooleate, filtering, washing the solid, and drying to obtain magnetic ferroferric oxide nanocrystals; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: adding magnetic ferroferric oxide nanocrystals to ethanol, adding silane coupling agent KH560, heating and stirring to react, centrifuging, washing, and drying to obtain modified magnetic ferroferric oxide nanocrystals; S3. Preparation of disalicylic aldehyde-triethylamine Schiff base: dissolving salicylaldehyde and triethylamine in toluene, heating under reflux for reaction, centrifuging, washing, and drying to obtain disalicylic aldehyde-triethylamine Schiff base; S4. Coupling: adding disalicylic aldehyde-triethylamine Schiff base and modified magnetic ferroferric oxide nanocrystals into ethanol, stirring for reaction, centrifuging, washing, and drying to obtain a disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystals complex; S5. Complexation of nickel and iron ions: dissolving nickel salt and iron salt in water, adding disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex, heating to reflux reaction, centrifuging, washing, and drying to obtain nickel / iron-disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex; S6. Oleic acid modification: Add nickel / iron-disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferrosoferric oxide nanocrystal complex into oleic acid, stir and mix evenly, filter and dry to obtain a heavy oil modification catalyst.

[0010] As a further improvement of the present invention, the iron salt in step S1 is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate, the mass ratio of the iron salt to sodium oleate is 2-3:5-7, the mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1-2:5-7:7-10, the temperature of the heating and stirring reaction is 65-75°C, the time is 3-5h, the solid-liquid ratio of the ferric oleate and petroleum ether is 1:5-7g / mL, and the paraffin is heated to a temperature of 300-400°C.

[0011] As a further improvement of the present invention, the mass ratio of the magnetic ferrosoferric oxide nanocrystals to the silane coupling agent KH560 in step S2 is 10:2-3, the temperature of the heating and stirring reaction is 40-50° C., and the time is 2-4 hours.

[0012] As a further improvement of the present invention, the molar ratio of salicylaldehyde to triethylamine in step S3 is 1.9-2:1, and the heating reflux reaction time is 3-5h.

[0013] As a further improvement of the present invention, in step S4, the mass ratio of the disalicylicaldehyde-triethylamine Schiff base to the modified magnetic ferrosoferric oxide nanocrystals is 3-4:10, and the stirring reaction time is 1-2 hours.

[0014] As a further improvement of the present invention, the nickel salt in step S5 is selected from at least one of nickel chloride, nickel nitrate, and nickel sulfate, the iron salt is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate, the mass ratio of the nickel salt, the iron salt, and the disalicylicaldehyde-triethylamine Schiff base @ modified magnetic ferrosoferric oxide nanocrystal composite is 2-3:3-4:15-20, and the heating reflux reaction time is 3-5h.

[0015] As a further improvement of the present invention, the mass ratio of the nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferrosoferric oxide nanocrystal composite and oleic acid in step S6 is 10-12:30-50.

[0016] The present invention further protects a heavy oil reforming catalyst prepared by the above preparation method.

[0017] The present invention further protects the use of the above-mentioned heavy oil reforming catalyst in reducing the viscosity of heavy oil.

[0018] The present invention has the following beneficial effects: The heavy oil in-situ catalytic upgrading technology injects catalysts and hydrogen donors into the formation, and with the help of the temperature and pressure conditions of the formation, the heavy oil undergoes a hydrogenation reaction in the formation, thereby transforming the macromolecular structure of the heavy oil into a small molecular structure with better fluidity, promoting the lightening of the heavy oil, and thus achieving an irreversible improvement in the fluidity of the heavy oil. After steam is injected into the formation, on the one hand, the higher temperature of the steam will heat the heavy oil and reduce its viscosity, and on the other hand, the steam will also cause the components in the heavy oil to undergo a lightening chemical reaction, thereby jointly promoting the improvement of the heavy oil recovery rate from two aspects.

[0019] The method comprises the following steps: firstly dissolving the prepared ferric oleate in petroleum ether, and then dripping the prepared ferric oleate into high-temperature paraffin. The high temperature causes the petroleum ether to volatilize rapidly, and the ferric oleate is thermally decomposed to generate ferroferric oxide. The ferroferric oxide nanocrystals are then prepared through liquid separation, washing, and drying. The nanocrystal material can be highly dispersed in heavy oil, significantly increases the specific surface area, and provides a large number of active sites to promote desulfurization and chain breaking reactions of heavy oil macromolecules, and can also promote hydrogen evolution reaction of nitrogen-hydrogen compounds, thereby improving the utilization efficiency of the hydrogen supply agent.

[0020] The surface of the prepared magnetic ferroferric oxide nanocrystals was modified by a silane coupling agent with an epoxy group, which could react with a bis-salicylaldehyde-triethylamine Schiff base. By controlling the molar ratio of salicylaldehyde and triethylamine, a bis-salicylaldehyde-triethylamine Schiff base was prepared. At the same time, an amino group was left to react with the epoxy group on the surface of the modified magnetic ferroferric oxide nanocrystals, thereby preparing a bis-salicylaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal composite. The nickel ions and iron ions were complexed by forming complex bonds, and Fe 3+ The catalyst mainly acts on colloids, saturated hydrocarbons and oxygen-containing groups, while Ni 2+ The catalyst mainly acts on asphaltenes, aromatic hydrocarbons and sulfur-containing groups. The formed complexes can cause the CS bonds, CN bonds, CO bonds, CC bonds, etc. in the oil to break, promote the disaggregation of asphaltene aggregates, and ultimately reduce the content of colloids and asphaltene.

[0021] The surface of the prepared nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex is then modified by coating with oleic acid. On the one hand, oleic acid can adhere to the surface of the nanoparticles, effectively preventing the aggregation of the nanoparticles, thereby producing better hydrothermal decomposition performance and cyclic durability. On the other hand, oleic acid can also form oleic iron and oleic nickel with nickel and iron ions to promote the cracking of heavy oil and the production of light hydrocarbons such as C2-C7 and CO2. After these components are dissolved in the heavy oil, the degree of reduction in the viscosity of the heavy oil is further improved.

[0022] The heavy oil reforming catalyst prepared by the invention has good hydrothermal decomposition performance and cycle durability, promotes the degradation of heavy oil, promotes the depolymerization of asphaltene aggregates, and finally reduces the content of colloid and asphaltene, thereby well reducing the viscosity of heavy oil, and has broad application prospects. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0024] This embodiment provides a method for preparing a heavy oil reforming catalyst, comprising the following steps: S1. Preparation of magnetic ferroferric oxide nanocrystals: 2g of ferric nitrate and 5g of sodium oleate were dissolved in 200mL of a mixed solvent, heated to 65°C, stirred for reaction for 3h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10g of ferrooleate was dissolved in 50mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to a temperature of 300°C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1:5:7; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: 10 g of magnetic ferroferric oxide nanocrystals were added to 200 mL of ethanol, 2 g of silane coupling agent KH560 was added, the mixture was heated to 40°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified magnetic ferroferric oxide nanocrystals; S3. Preparation of disalicylic aldehyde-triethylamine Schiff base: 19 mmol salicylaldehyde and 10 mmol triethylamine were dissolved in 100 mL toluene, heated under reflux for 3 h, centrifuged, washed, and dried to obtain disalicylic aldehyde-triethylamine Schiff base; S4. Coupling: 3 g of salicylaldehyde-triethylamine Schiff base and 10 g of modified magnetic ferroferric oxide nanocrystals were added to 100 mL of ethanol, stirred for 1 h, centrifuged, washed, and dried to obtain a salicylaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex; S5. Complexation of nickel and iron ions: 2 g nickel nitrate and 3 g iron nitrate were dissolved in 200 mL water, 15 g disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex was added, and the mixture was heated under reflux for 3 h, centrifuged, washed, and dried to obtain nickel / iron-disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex; S6. Oleic acid modification: 10 g of nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferrosoferric oxide nanocrystalline complex was added to 30 g of oleic acid, stirred and mixed for 15 min, filtered, and dried to obtain a heavy oil modification catalyst. Example 2

[0025] This embodiment provides a method for preparing a heavy oil reforming catalyst, comprising the following steps: S1. Preparation of magnetic ferroferric oxide nanocrystals: 3g of ferric sulfate and 7g of sodium oleate were dissolved in 200mL of a mixed solvent, heated to 75°C, stirred for reaction for 5h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10g of ferrooleate was dissolved in 70mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to 400°C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 2:7:10; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: 10 g of magnetic ferroferric oxide nanocrystals were added to 200 mL of ethanol, 3 g of silane coupling agent KH560 was added, the mixture was heated to 50° C., stirred for 4 h, centrifuged, washed, and dried to obtain modified magnetic ferroferric oxide nanocrystals; S3. Preparation of disalicylic aldehyde-triethylamine Schiff base: 20 mmol of salicylaldehyde and 10 mmol of triethylamine were dissolved in 100 mL of toluene, heated under reflux for 5 h, centrifuged, washed, and dried to obtain disalicylic aldehyde-triethylamine Schiff base; S4. Coupling: 4 g of salicylaldehyde-triethylamine Schiff base and 10 g of modified magnetic ferroferric oxide nanocrystals were added to 100 mL of ethanol, stirred for 2 h, centrifuged, washed, and dried to obtain a salicylaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex; S5. Complexation of nickel and iron ions: 3 g of nickel sulfate and 4 g of iron sulfate were dissolved in 200 mL of water, and 20 g of disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex was added, and the mixture was heated under reflux for 5 h, centrifuged, washed, and dried to obtain nickel / iron-disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex; S6. Oleic acid modification: 12 g of nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferrosoferric oxide nanocrystalline complex was added to 50 g of oleic acid, stirred and mixed for 15 min, filtered, and dried to obtain a heavy oil modification catalyst. Example 3

[0026] This embodiment provides a method for preparing a heavy oil reforming catalyst, comprising the following steps: S1. Preparation of magnetic ferroferric oxide nanocrystals: 2.5 g of ferric chloride and 6 g of sodium oleate were dissolved in 200 mL of a mixed solvent, heated to 70 ° C, stirred for 4 h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10 g of ferrooleate was dissolved in 60 mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to a temperature of 350 ° C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1.5:6:8; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: 10 g of magnetic ferroferric oxide nanocrystals were added to 200 mL of ethanol, 2.5 g of silane coupling agent KH560 was added, the mixture was heated to 45°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified magnetic ferroferric oxide nanocrystals; S3. Preparation of disalicylic aldehyde-triethylamine Schiff base: 19.5mmol salicylaldehyde and 10mmol triethylamine were dissolved in 100mL toluene, heated under reflux for 4h, centrifuged, washed, and dried to obtain disalicylic aldehyde-triethylamine Schiff base; S4. Coupling: 3.5 g of salicylaldehyde-triethylamine Schiff base and 10 g of modified magnetic ferroferric oxide nanocrystals were added to 100 mL of ethanol, stirred for 1.5 h, centrifuged, washed, and dried to obtain a salicylaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex; S5. Complexation of nickel and iron ions: 2.5 g nickel chloride and 3.5 g ferric chloride were dissolved in 200 mL water, 17 g disalicyclic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex was added, and the mixture was heated under reflux for 4 h, centrifuged, washed, and dried to obtain nickel / iron-disalicyclic aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex; S6. Oleic acid modification: 11 g of nickel / iron-disalicylic aldehyde-triethylamine Schiff base@modified magnetic ferrosoferric oxide nanocrystalline complex was added to 40 g of oleic acid, stirred and mixed for 15 min, filtered, and dried to obtain a heavy oil modification catalyst.

[0027] Comparative Example 1 Compared with Example 3, the difference is that step S2 is not performed.

[0028] The details are as follows: S1. Preparation of magnetic ferroferric oxide nanocrystals: 2.5 g of ferric chloride and 6 g of sodium oleate were dissolved in 200 mL of a mixed solvent, heated to 70 ° C, stirred for 4 h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10 g of ferrooleate was dissolved in 60 mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to a temperature of 350 ° C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1.5:6:8; S2. Preparation of disalicylicaldehyde-triethylamine Schiff base: 19.5mmol salicylaldehyde and 10mmol triethylamine were dissolved in 100mL toluene, heated under reflux for 4h, centrifuged, washed, and dried to obtain disalicylicaldehyde-triethylamine Schiff base; S3. Mixing: 3.5 g of salicylaldehyde-triethylamine Schiff base and 10 g of magnetic ferrosoferric oxide nanocrystals were mixed for 10 min to obtain a salicylaldehyde-triethylamine Schiff base-modified magnetic ferrosoferric oxide nanocrystal mixture; S4. Complexation of nickel and iron ions: 2.5 g of nickel chloride and 3.5 g of ferric chloride were dissolved in 200 mL of water, 17 g of a mixture of disalicylic aldehyde-triethylamine Schiff base-modified magnetic ferroferric oxide nanocrystals was added, and the mixture was heated under reflux for 4 h, centrifuged, washed, and dried to obtain a mixture of nickel / iron-disalicylic aldehyde-triethylamine Schiff base-modified magnetic ferroferric oxide nanocrystals; S5. Oleic acid modification: 11 g of a mixture of nickel / iron-disalicylicaldehyde-triethylamine Schiff base-modified magnetic ferrosoferric oxide nanocrystals was added to 40 g of oleic acid, and the mixture was stirred for 15 min, filtered, and dried to obtain a heavy oil modification catalyst.

[0029] Comparative Example 2 Compared with Example 3, the difference is that nickel chloride is not added in step S5.

[0030] The details are as follows: S5. Complexation of iron ions: Dissolve 6 g of ferric chloride in 200 mL of water, add 17 g of disalicylic acid aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex, heat and reflux for 4 h, centrifuge, wash, and dry to obtain iron-disalicylic acid aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex.

[0031] Comparative Example 3 Compared with Example 3, the difference is that ferric chloride is not added in step S5.

[0032] The details are as follows: S5. Complexation of nickel ions: Dissolve 6 g of nickel chloride in 200 mL of water, add 17 g of disalicylic acid aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex, heat and reflux for 4 h, centrifuge, wash, and dry to obtain nickel-disalicylic acid aldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex.

[0033] Comparative Example 4 Compared with Example 3, the difference is that steps S3 to S5 are not performed.

[0034] The details are as follows: S1. Preparation of magnetic ferroferric oxide nanocrystals: 2.5 g of ferric chloride and 6 g of sodium oleate were dissolved in 200 mL of a mixed solvent, heated to 70 ° C, stirred for 4 h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10 g of ferrooleate was dissolved in 60 mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to a temperature of 350 ° C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1.5:6:8; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: 10 g of magnetic ferroferric oxide nanocrystals were added to 200 mL of ethanol, 2.5 g of silane coupling agent KH560 was added, the mixture was heated to 45°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified magnetic ferroferric oxide nanocrystals; S3. Oleic acid modification: 11 g of modified magnetic ferrosoferric oxide nanocrystalline composite was added to 40 g of oleic acid, stirred and mixed for 15 min, filtered, and dried to obtain a heavy oil modification catalyst.

[0035] Comparative Example 5 Compared with the embodiment 3, the difference is that step S6 is not performed.

[0036] The details are as follows: S1. Preparation of magnetic ferroferric oxide nanocrystals: 2.5 g of ferric chloride and 6 g of sodium oleate were dissolved in 200 mL of a mixed solvent, heated to 70 ° C, stirred for 4 h, allowed to stand for separation, the upper reddish brown liquid was washed with water, the solvent was removed under reduced pressure to obtain ferrooleate, 10 g of ferrooleate was dissolved in 60 mL of petroleum ether to obtain a petroleum ether solution of ferrooleate, paraffin was heated to a temperature of 350 ° C, the petroleum ether solution of ferrooleate was added dropwise, filtered, the solid was washed, and dried to obtain magnetic ferroferric oxide nanocrystals; The mixed solvent is ethanol, cyclohexane and water in a volume ratio of 1.5:6:8; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: 10 g of magnetic ferroferric oxide nanocrystals were added to 200 mL of ethanol, 2.5 g of silane coupling agent KH560 was added, the mixture was heated to 45°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified magnetic ferroferric oxide nanocrystals; S3. Preparation of disalicylic aldehyde-triethylamine Schiff base: 19.5mmol salicylaldehyde and 10mmol triethylamine were dissolved in 100mL toluene, heated under reflux for 4h, centrifuged, washed, and dried to obtain disalicylic aldehyde-triethylamine Schiff base; S4. Coupling: 3.5 g of salicylaldehyde-triethylamine Schiff base and 10 g of modified magnetic ferroferric oxide nanocrystals were added to 100 mL of ethanol, stirred for 1.5 h, centrifuged, washed, and dried to obtain a salicylaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal complex; S5. Complexation of nickel and iron ions: Dissolve 2.5g nickel chloride and 3.5g ferric chloride in 200mL water, add 17g disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex, heat and reflux for 4h, centrifuge, wash and dry to obtain nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex, which is a heavy oil modification catalyst.

[0037] Test Example 1 Weigh the marine oil sample and Shengli heavy oil (components shown in Table 1) and put them into a high-temperature and high-pressure reactor, add 0.5wt% of the heavy oil reforming catalyst prepared in Examples 1-3 or Comparative Examples 1-5, and after the sealing and airtightness inspections are qualified, heat and stir, keep the temperature constant for a specified time, stop stirring, and cool to room temperature. Compare the viscosity of the oil sample before and after the catalytic reaction, and calculate the viscosity reduction rate of the heavy oil.

[0038] Table 1 ; The results are shown in Table 2.

[0039] Table 2 ; It can be seen from the above table that the heavy oil reforming catalysts prepared in Examples 1-3 of the present invention have a good viscosity reducing effect on heavy oil.

[0040] Test Example 2 Contact Angle Test The heavy oil reforming catalyst prepared in Examples 1-3 or Comparative Examples 1-5 was added to petroleum ether to prepare a 5wt% suspension, and ultrasonically dispersed uniformly. The mixture was evenly dropped onto the surface of a glass slide, dried the solvent, and cooled naturally. The contact angles of water droplets and liquid paraffin droplets on the surface were measured using a DSA100 contact angle measuring instrument (tested after 3 minutes of equilibrium). The results are shown in Table 3.

[0041] Table 3 ; It can be seen from the above table that the heavy oil reforming catalysts prepared in Examples 1-3 of the present invention have weak hydrophilicity and strong lipophilicity. The weak hydrophilicity enables it to be well dispersed in water and easily injected into the ground, and the strong lipophilicity enables it to easily migrate spontaneously to the oil-water interface. After the catalyst is adsorbed on the oil-water interface, the catalyst active center is efficiently carried to the oil phase, thereby exerting a catalytic viscosity reduction effect.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a heavy oil reforming catalyst, characterized in that: After preparing magnetic ferroferric oxide nanocrystals, the surface is modified by epoxy silane coupling agent, coupled with disalicylic aldehyde-triethylamine Schiff base, then complexed with nickel and iron ions, and coated with oleic acid to obtain a heavy oil reforming catalyst, which includes the following steps: S1. Preparation of magnetic ferroferric oxide nanocrystals: dissolving iron salt and sodium oleate in a mixed solvent, heating and stirring to react, standing to separate the liquids, washing the upper reddish brown liquid with water, removing the solvent under reduced pressure to obtain iron oleate, dissolving iron oleate in petroleum ether to obtain a petroleum ether solution of iron oleate, heating paraffin, dropping the petroleum ether solution of iron oleate, filtering, washing the solid, and drying to obtain magnetic ferroferric oxide nanocrystals; the iron salt is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate, and the mass ratio of the iron salt to sodium oleate is 2-3:5-7; S2. Preparation of modified magnetic ferroferric oxide nanocrystals: adding magnetic ferroferric oxide nanocrystals to ethanol, adding silane coupling agent KH560, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified magnetic ferroferric oxide nanocrystals; the mass ratio of the magnetic ferroferric oxide nanocrystals to the silane coupling agent KH560 is 10:2-3; S3. Preparation of disalicylicaldehyde-triethylamine Schiff base: dissolving salicylaldehyde and triethylamine in toluene, heating under reflux for reaction, centrifuging, washing, and drying to obtain disalicylicaldehyde-triethylamine Schiff base; the molar ratio of salicylaldehyde to triethylamine is 1.9-2:1; S4. Coupling: adding disalicylicaldehyde-triethylamine Schiff base and modified magnetic ferroferric oxide nanocrystals into ethanol, stirring for reaction, centrifuging, washing, and drying to obtain a disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystal composite; the mass ratio of the disalicylicaldehyde-triethylamine Schiff base to the modified magnetic ferroferric oxide nanocrystal is 3-4:10; S5. Complexation of nickel and iron ions: dissolving nickel salt and iron salt in water, adding salicylaldehyde-triethylamine Schiff base @ modified magnetic ferroferric oxide nanocrystalline complex, heating to reflux reaction, centrifuging, washing, and drying to obtain nickel / iron-salicylaldehyde-triethylamine Schiff base @ modified magnetic ferroferric oxide nanocrystalline complex; the mass ratio of the nickel salt, iron salt, salicylaldehyde-triethylamine Schiff base @ modified magnetic ferroferric oxide nanocrystalline complex is 2-3:3-4:15-20; S6. Oleic acid modification: Add nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex to oleic acid, stir and mix evenly, filter, and dry to obtain a heavy oil modification catalyst; the mass ratio of the nickel / iron-disalicylicaldehyde-triethylamine Schiff base@modified magnetic ferroferric oxide nanocrystalline complex to oleic acid is 10-12:30-50.

2. The preparation method according to claim 1, characterized in that: The mixed solvent in step S1 is ethanol, cyclohexane and water in a volume ratio of 1-2:5-7:7-10, the temperature of the heating and stirring reaction is 65-75°C, the time is 3-5h, the solid-liquid ratio of the iron oleate and petroleum ether is 1:5-7g / mL, and the paraffin is heated to a temperature of 300-400°C.

3. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S2 is 40-50° C. and the time is 2-4 hours.

4. The preparation method according to claim 1, characterized in that: The heating reflux reaction time in step S3 is 3-5h.

5. The preparation method according to claim 1, characterized in that: The stirring reaction time in step S4 is 1-2h.

6. The preparation method according to claim 1, characterized in that: In step S5, the nickel salt is selected from at least one of nickel chloride, nickel nitrate, and nickel sulfate, the iron salt is selected from at least one of ferric chloride, ferric sulfate, and ferric nitrate, and the heating reflux reaction time is 3-5 hours.

7. A heavy oil upgrading catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the heavy oil upgrading catalyst as claimed in claim 7 in reducing the viscosity of heavy oil.

Citation Information

Patent Citations

  • Method for integrally catalyzing, reforming, reducing viscosity, extracting and transporting thick oil

    CN101649734A

  • Preparation method of small particle size ferroferric oxide magnetic nano particles

    CN108285176A

  • Preparation method for loading nanocrystalline metal oxide

    CN109092286A

  • Graphene-Schiff base nickel compound for solid propellant and preparation method thereof

    CN110981651A

  • Magnetic nano composite material for ATRP reaction and preparation method of magnetic nano composite material

    CN111100161A